CO2 ABSORBENTS: A REVIEW OF THE LATEST LITERATURE AND THEIR APPLICATIONS - Andriana Indira Lestari; Susan Azizah Aprilian; Tiana Adelia Paramitha; Asep Kadarohman (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), Politeknik Negeri Cilacap, 2026)
Increased concentrations of carbon dioxide (CO₂) in the atmosphere due to anthropogenic activities necessitate the development of effective mitigation technologies, such as Carbon Capture, Utilization, and Storage (CCUS). This article aims to analyze the development and performance of various types of absorbents in the CO₂ capture process, both through chemical absorption and adsorption. The literature search method was conducted using Google Scholar, Elsevier, ScienceDirect, and Scopus with the keywords carbon capture, amines, K2CO3, and CO2 absorbents from 2015 to 2025. The articles obtained were selected based on their relevance to the topic of CO2 absorbents, and 20 articles supporting this topic were found. The results of the literature review show that chemical adsorbents such as monoethanolamine (MEA) and potassium carbonate (K₂CO₃) are still the main choices in industrial applications due to their efficiency and stability. MEA can achieve an absorption efficiency of up to 87.14%, while K₂CO₃ can achieve an efficiency of up to 69.45%. It was found that the optimal strategy for CO₂ mitigation in the future lies in a combination of established conventional chemical absorption technology and innovations in economical and sustainable biomass-based adsorbent materials, supported by digital process modeling for optimization. Keywords: Absorption, CCUS, K₂CO₃, MEA, Carbon Capture.